METHODOLOGY FOR THE FORMATION OF THE CONCEPT OF PARTS OF SPEECH IN PUPILS OF GENERAL SECONDARY EDUCATION - Gulyamova X. (Bright Mind Publishing, 2025)
The article examines the grammatical classification of words based on their lexical-semantic, morphological properties and syntactic functions, as well as its teaching to students of comprehensive secondary schools in native language lessons.
Keywords: Word class, grammatical classification of words, order of analysis, didactic principle, morphological concept, conversation method, problem-based research method, lexical-grammatical difference of words.